The translation profession: centres and peripheries - Dam, Helle V.; Koskinen, Kaisa (The Journal of Specialised Translation, 2016)
This article introduces a special issue on the translation profession. Its point of departure is that translation constitutes an entity of practice that is sufficiently stable to be identified, defined and delimited from other entities of practice, but also that its boundaries are porous and unstable and that the people and artefacts that inhabit it, its agents, are in constant movement between its centre and peripheries. Against this backdrop and departing from various vantage points, the contributors and editors of the special issue explore the topology of this entity, here referred to as the translation profession following current usage in the field, focusing on its centre-periphery relations and the way these relations have developed over time and currently seem to be developing. The introduction gives an overview of the articles in the special issue and identifies and discusses key topics and concepts foregrounded by the authors in response to the call for papers. Key topics include professionalisation, assumed threats to professional status, professional boundaries, and insiders and outsiders.